Management of Mosque Management Communication in the Management of Islamic Holidays Commemoration (PHBI) at the Jami' Istiqlal Mosque Palembang - Intan Kusuma Rahmadhani; Henny Yusalia; M. Mifta Farid (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research, entitled "Communication Management of Mosque Administration in Managing Islamic Holy Day Celebrations (PHBI) at Masjid Jami' Istiqlal Palembang", which aims to determine how communication management is implemented by the management of Masjid Jami' Istiqlal Palembang in organizing Islamic Holy Day Celebrations (PHBI). Masjid Jami' Istiqlal is one of the community-based mosques in Palembang that actively holds religious activities, yet still faces several challenges, particularly in coordination and internal communication among its management members. This research uses a descriptive qualitative approach with Henri Fayol's classical management theory, which includes four main functions: planning, organizing, actuating, and controlling. The data were collected through interviews, observations, and documentation involving mosque administrators, the PHBI coordinator, and related parties. The results show that the communication management within Masjid Jami' Istiqlal has been carried out but not optimally. In the planning function, meetings and activity programs are arranged collaboratively, though constrained by coordination and funding issues. In organizing, the committee structure is well-formed but inconsistently implemented. The actuating function runs effectively in certain periods, but communication weakens when the PHBI coordinator is less active. In controlling, evaluation and reporting processes are not yet conducted regularly. The main obstacles include weak coordination, limited cross-department communication, and insufficient human and financial resources. Overall, the implementation of communication management at Masjid Jami' Istiqlal Palembang reflects participatory and collaborative values among the mosque management and congregation. However, improvements are needed in coordination and consistency to ensure that PHBI activities can be carried out more effectively and sustainably in the future.